The methods of treatment of long fractures and physiological fundamentals of osteosynthesis (the dynamics of views and modern state-of-art) - Bets, Grygorii; Bets, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The spreading of AO philosophy, the traditions of native orthopedics-traumatology school and socio-economic peculiarities of the country have influenced on the tactics and technology of the treatment bone fractures in Ukraine. Simultaneously with modern AO technique skeletal traction and fixation method are used but the indications for their application are still uncertain. It was noticed many decades ago, that success of treatment is strongly correlated with early functioning of injured segment. The criteria of functionality of technology are still among the main ones to define the degree of its correspondence to the principles of physiological treatment of fractures. It was noticed, that osteosynthesis is considered as successful if it does not require any additional external fixation, allow early function and minimize negative influence on the vitality of damaged tissues. Tactical-technological items of fracture treatment require an analysis and reconsideration taking into consideration the state of orthopedics-traumatology service in Ukraine concerning the supply of high-grade licensed fixators and instruments for osteosynthesis, equipment for intraoperative radiographic monitoring and theoretical and practical training of specialists. The method of skeletal traction is still being used to treat inoperable patients and on the stages of preoperative preparation and planning. The fixing bandages and orthesises are the necessary components in complex treatment of trauma patients as the main immobilizing means and patient-specific functional orthesises to provide early functional rehabilitation. It’s emphasize, that the use of AO technology should not exclude from practice the method of external fixation that has no alternatives in the treatment of complications, open and gunshot fractures. The absence of serial production of external fixators influenced negatively on the quality of treatment of war casualties from South East part of Ukraine.